1992
DOI: 10.1524/ract.1992.57.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Particle Induced Reactions of 209Bi at 55.7 and 58.6 MeV

Abstract: The alpha particle induced reaction studies of 209 Bi have been carried out at alpha particle energies of 55.7 MeV and 58.6 MeV using gamma ray spectrometry. The cross sections for the production of reaction products 207 At, 208 At, 209 At and 210 At have been determined. The variation of experimental production cross section for the reaction products in 209 Bi(a,xn) 213 " Jt At as a function of neutron number of the reaction products at different available energies showed the presence of possible shell effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The diffi- culty to simulate astatine production from a lead-bismuth target comes first of all from the two production channels. The first one is related to the emission of one and only one π − in the interaction between the proton beam and a bismuth nucleus, 209 Bi(p, π − xn) 210−x At, and the second one brings into play the secondary helium nuclei, mostly the α, via 209 Bi( 3 He,xn) 212−x At and 209 Bi(α,xn) 213−x At, and with an incident energy below around 100 MeV [282][283][284][285][286][287][288][289][290][291][292][293]. In [137] new calculations are reported with the version INCL4.6.…”
Section: Megapie (Megawatt Pilotmentioning
confidence: 99%
“…The diffi- culty to simulate astatine production from a lead-bismuth target comes first of all from the two production channels. The first one is related to the emission of one and only one π − in the interaction between the proton beam and a bismuth nucleus, 209 Bi(p, π − xn) 210−x At, and the second one brings into play the secondary helium nuclei, mostly the α, via 209 Bi( 3 He,xn) 212−x At and 209 Bi(α,xn) 213−x At, and with an incident energy below around 100 MeV [282][283][284][285][286][287][288][289][290][291][292][293]. In [137] new calculations are reported with the version INCL4.6.…”
Section: Megapie (Megawatt Pilotmentioning
confidence: 99%
“…These phenomena are due to the increase of multi-nucleon emission and multi-chance fission probability with an increase of excitation energy. However, the bremsstrahlung energy dependency of the FWHM and the average mass of the mass-yield distribution is different from those of particle-induced fission [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. This is most probably due to the fact that the fission product yields in charged particle-induced fission were also affected by an input angular momentum of the excitation energy.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the mass-yield distributions for both charged particle-and bremsstrahlung-induced fission of Au, Pb, and Bi are symmetric. It has been also observed that the full width at half maximum (FWHM) of the mass-yield distribution in the charged particle-induced fission of 209 Bi [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] increases from 17 mass units for [15][16][17][18][19][20][21][22] MeV deuteron-induced fission [25] to 24 mass units for the [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] MeV helium-induced fission [19][20][21]. The FWHM of the mass-yield...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13 data sets were found in literature: [121][122][123][124][125][126][127][128][129][130][131][132] (two data sets were reported in [126,127]: by direct measurement and through decay of 210 Po). Available data are compared with TENDL evaluations in Fig.…”
Section: Bi(α3n) 210 At Reactionmentioning
confidence: 99%